Anti-microbial surfaces by plasma assisted immobilization of chitosan. - Toh, Daniel Seng Wei. (2010)
This report presents the methods and processes involved in the development of an anti-microbial coating of quaternized chitosan on a glass surface. The antimicrobial effect of the quaternized chitosan was tested against a variety of bacteria such as Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa as well as fungi such as Candida albicans and Fusarium solani to verify its anti-microbial property against micro-organisms. The anti-microbial coating was applied by two step plasma treatment (TSPT) using Argon plasma to immobilize quaternized chitosan on the glass surface. The anti-microbial property of the coating was tested against bacterial Escherichia coli and the results showed that the quaternized chitosan immobilized surface was capable of killing the bacteria. Using design of experiments technique, the effects of power and time duration of each of the 2 steps of the plasma treatment process was investigated. It was determined that power used in the second step and time duration of the first step was significant. In addition, there was a significant interaction between the power used in the first step and time duration of the second step. The plasma treated surface was also examined by contact angle measurement and the surface characterized using atomic force microscopy.